Sustainable Development in Norway on the example of Government Pension Fund Global - Julita Fiedorczuk (Copernican Journal of Finance & Accounting, 2015)
This article is an attempt to assess the functioning of the Norwegian Government Pension Fund Global in relation to the degree of implementation of the concept’s objectives of sustainable development. The aim of the article apart from this assessment is to determine significance and the benefits of the concept to the Fund and the country. To apply the hypothetical-deductive method. The concept of sustainable development has a relatively long history in Norway. Sustainable development is not just a dead regulation, but a way of thinking Norwegians. Social awareness of balance need causes of naturalness of reconciling the economic, social and environmental interest in economy. On the one hand, Fund acting within state structures, is the implementing tool of sustainable development policy. On the other, the Fund uses assumptions of the concept to achieve sustainable economic benefits. Maturity sustainable activities of the Fund contributes to the achievement of competitive advantage among other funds. The Fund is the largest Government Pension Fund in the world in terms of net assets, of which the largest part of the market value is an inflow of capital from outside. Investors deposit their funds in it because they trust to management style. Due to the global character, size and geographical or investment diversification, manifestation of sustainable practices reaches to wide-spectrum of recipients. The range of message builds the Fund and country reputation that actively suggests the only one way to sustainable development.